Characterization of Vegetation Changes in Jiangsu Coastal Wetlands and Analysis of Their Causes - LYU Lin; YU Lingcheng; QIAN Linfeng; CHEN Yanyan; ZHANG Ke; GU Rong; ZHANG Dong (Haiyang Kaifa yu guanli)
In the paper, using a combination of object-oriented image segmentation and random forest classification, the spatial distribution information of Jiangsu coastal wetland ecosystems in 2011, 2016 and 2021 was extracted based on Landsat and Sentinel-2 satellite images, and the spatiotemporal dynamic changes of the wetland vegetation communities and the causes of wetland vegetation changes were analyzed. The results show that the classification accuracy based on Sentinel-2 satellite images is high. The vegetation community of Jiangsu coastal wetland is mainly distributed between Xinyang Port and Doulong Port, with a few coastal embankments distributed in strips. The vegetation types are mainly Spartina alterniflora, Suaeda salsa, and Phragmites australis. From 2011 to 2021, the vegetation of Jiangsu coastal wetland shows the state of decreasing and then increasing. The human activities, such as the reclamation of wetland and the process of urbanization, are the reasons of the area shrinkage. At the same time, the expansion of Spartina alterniflora and the implementation of policies of wetland protection and restoration make the wetland area increase continuously.